ANALISIS SAINS SEBAGAI CARA BERPIKIR PADA BUKU TEMATIK SISWA KELAS V SD - Sholiha Nurfaidah, Siti; Lukman Praja, Azis; Nurhadi, Moh. (STKIP Subang, 2021)
Literacy of science is very important to be mastered by each individual to be able to adapt to the progress of science and technology in the future. One attempt to improve the ability of science literacy through the analysis of textbooks lessons. The type of research used is descriptive, by collecting data in the form of documentation study. The sample in this research is several pages of analyzed books taken in a random way using multistage sampling technique. The results show 21% of the book presents the aspect of science as a way of thinking. The aspect is presented on the entire theme of the book with various values. In themes 1 and 2 this aspect is often presented that is equal to 71%, and 51%. The following findings show that Book Y simply presents aspects of science as a way of thinking. In other words, Book Y is enough to emphasize material that supports the mastery of the process.